Women and green entrepreneurship: a literature based study of India. (3rd June 2020) - Potluri, Seema; Phani, B.V.
Accelerated economic globalisation over the last two decades with its environmental impact has brought to the fore the criticality of thinking green in terms of consumption and production for long term sustainability the world over. The above, combined with economic transition from planned economy to a market economy in developing economies, has put pressure on the existing social structures impacting gender disparity and economic empowerment of women. This impact has primarily benefited the middle class where basic needs of women were catered to and they had easier access to formal education. Literature in this domain indicates that these women would be predisposed towards entrepreneurship so as to balance their social and career obligations. It has been proposed and an argument is made that there would be a higher propensity of these women to adopt ecopreneurship due to their inherent social conditioning with minimum incentives and the innate desire to care for the environment can be a defining force in furthering 'ecopreneurship'.